Extractive desulfurization using Fe-Containing ionic liquids - Ko, Nan Hee; Lee, Je Seung; Huh, Eun Soo; Lee, Hyunjoo; Jung, Kwang Deog; Kim, Hoon Sik; Cheong, Minserk (AMER CHEMICAL SOC, 2008)
Fe-III-containing ionic liquids (ILs), prepared from the reaction of anhydrous FeCl3 and imidazolium chloride ([limidazolium]Cl), were used as effective extractants for he desulfurization of a model oil containing dibenzothiophene (DBT). The amount of DBT extracted increased with an increasing molar ratio of FeCl3/ [imidazolium]Cl. The ability of the ILs to extract DBT seems to be attributed to the combined effects of Lewis acidity and fluidity of ILs.
Keywords: OIL REFINERY STREAMS; OXIDATIVE DESULFURIZATION; DEEP DESULFURIZATION; HYDRODESULFURIZATION; CATALYSTS; GASOLINE; DIBENZOTHIOPHENES; DENITROGENATION; REACTIVITIES; PRESSURE